A Medium-Term Venous Access Alternative for Infants Undergoing Congenital Heart Surgery. Issue 1 (January 2018) - Raees, Muhammad Aanish; Dubar, Paul V.; Bichell, David P.
We describe a strategy aimed at maximizing the safety and minimizing the thrombogenicity of central venous lines for neonates with congenital heart defects. Our method involves the use of a tunneled technique to place a 4.2 Fr single-lumen (Broviac) catheter in the subpericardial space, with minimal intravascular course and a tip placed in the lower right atrium. Using this technique, we potentially eliminated the requirement for percutaneous placement of central venous lines postoperatively as well as potentially decreased the risk of intrapericardial bleeding associated with transthoracic lines.